Perceptions and Experiences of Learners about Online Learning in the Secondary Schools - Singh, Vandana (JOURNAL OF INDIAN EDUCATION, 2022)
Pandemic has successfully forced global shutdown of several activities, including educational activities. As a response to the crisis of continuing learning, almost all the educational institutions have opted for online education. Remote learning, home learning, online learning are the alternative learning methods for classroom learning. This study was conducted to find out the perception of learners towards online education and it also tried to explore various attributes of online classes such as presentation of academic content, resolving a queries challenges, etc. It also took into account the issues related to the availability of devices and internet connection, which are helpful in designing an effective online environment. The findings of the study indicated that most of the learners have a positive perception about online learning to continue their studies. The students however, felt the need of providing flexibility in the time schedule of the classes. They also believed that online learning is stressful both physically and mentally as it affects the health and their social life. It is argued in the paper that online learning must be cautiously designed keeping in mind the pedagogical considerations, while instructional activities have to become hybrid. In order to adjust with this new normal, educational systems have to adopt blended learning in a much rigorous way. The lessons which are learnt now in the form of challenges have to be optimally converted into opportunities.